2011
DOI: 10.3928/01477447-20110714-06
|View full text |Cite
|
Sign up to set email alerts
|

Is Repetitive Intraoperative Splash Basin Use a Source of Bacterial Contamination in Total Joint Replacement?

Abstract: Splash basins are used in arthroplasty cases to wash instruments. Several studies in the literature have shown these basins being a potential source of bacterial infection. This study assesses the risk of contamination of intraoperative splash basins used to wash and store instruments. A total of 46 random clean primary arthroplasty cases (32 hips, 13 knees, and 1 unicondylar knee) were studied by taking cultures of sterile splash basins as soon as they are opened (controls) and again at wound closure after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
1
21
1
Order By: Relevance
“…2 previous studies, where water taken from the splash basin was passed through a grid membrane and the membrane filter was then cultured, gave contamination rates of 74% (Baird et al 1984) and 24% (Anto et al 2006). A recent study in which swabs were used to take cultures from the splash basin found a contamination rate of only 2% (Glait et al 2011), and the authors speculated that the discrepancy might be partly due to differences in sampling methods—but our findings do not support this. To our knowledge, there have been no studies that have clearly linked the splash basin to infection.…”
Section: Discussioncontrasting
confidence: 98%
“…2 previous studies, where water taken from the splash basin was passed through a grid membrane and the membrane filter was then cultured, gave contamination rates of 74% (Baird et al 1984) and 24% (Anto et al 2006). A recent study in which swabs were used to take cultures from the splash basin found a contamination rate of only 2% (Glait et al 2011), and the authors speculated that the discrepancy might be partly due to differences in sampling methods—but our findings do not support this. To our knowledge, there have been no studies that have clearly linked the splash basin to infection.…”
Section: Discussioncontrasting
confidence: 98%
“…Splash basin contamination has been reported in the literature to range from 2% to 74% [58][59][60] . Irrigation fluid on the back table may also become contaminated over time.…”
Section: The Back Table (Fluids and Instruments)mentioning
confidence: 99%
“…9 Regarding the containers for the irrigation solution at the procedure field, one study showed that in 13 of 21 irrigating solutions in containers were contaminated at the end of the surgical procedures. [10][11][12] Our experience recommends the use of sterile devices and adapters to avoid contamination of the solution and hence reduce SSI incidence.…”
Section: 3mentioning
confidence: 99%
“…9 Regarding the containers for the irrigation solution at the procedure field, one study showed that in 13 of 21 irrigating solutions in containers were contaminated at the end of the surgical procedures. [10][11][12] Our experience recommends the use of sterile devices and adapters to avoid contamination of the solution and hence reduce SSI incidence.The Food and Drugs Administration (FDA) has warned the inappropriate use of antibiotics in surgical wound irrigation as it increases antimicrobial resistance and reduces the effectiveness of established antibiotic treatments and increased health costs and mortality. 13,14 The antiseptics are also commonly used (the most common one is the iodopovidone) in the surgical wound irrigation to exert a bactericidal effect, but it also lacks FDA's authorization.…”
mentioning
confidence: 99%